Rapid extraction of high- and low-density microplastics from soil using high-gradient magnetic separation - Ramage, Stuart J.F.F.; Pagaling, Eulyn; Haghi, Reza K.; Dawson, Lorna A.; Yates, Kyari; Prabhu, Radhakrishna; Hillier, Stephen; Devalla, Sandhya (The Science of the total environment, 2022)
Microplastics (MPs) are present in all environments, and concerns over their possible detrimental effects on flora and fauna have arisen. Density separation (DS) is commonly used to separate MPs from soils to allow MP quantification; however, it frequently fails to extract high-density MPs sufficiently, resulting in under-estimation of MP abundances. In this proof-of-concept study, a novel three-stage extraction method was developed, involving high-gradient magnetic separation and removal of magnetic soil (Stage 1), magnetic tagging of MPs using surface modified iron nanoparticles (Stage 2), and high-gradient magnetic recovery of surface-modified MPs (Stage 3). The method was optimised for four different soil types (loam, high‑carbon loamy sand, sandy loam and high-clay sandy loam) spiked with different MP types (polyethylene, polyethylene terephthalate, and polytetrafluoroethylene) of different particle sizes (63 μm to 2 mm) as well as polyethylene fibres (2–4 mm). The optimised method achieved average recoveries of 96% for fibres and 92% for particles in loam, 91% for fibres and 87% for particles in high‑carbon loamy sand, 96% for fibres and 89% for particles in sandy loam, and 97% for fibres and 94% for particles in high-clay sandy loam. These were significantly higher than recoveries achieved by DS, particularly for fibres and high-density MPs (p < 0.05). To demonstrate the practical application of the HGMS method, it was applied to a farm soil sample, and high-density MP particles were only recovered by HGMS. Furthermore, this study showed that HGMS can recover fibre-aggregate complexes. This improved extraction method will provide better estimates of MP quantities in future studies focused on monitoring the prevalence of MPs in soils. [Display omitted] •Rapid High-Gradient Magnetic Separation method for microplastic extraction from soil•The HGMS method performed significantly better than the density separation method.•It was able to recover high- and low-density microplastics.•Could recover microplastic particles and fibres 63 μm–15 mm in size (≥ 87%)•Avoided the use and disposal of hazardous salts associated with density separation